Antecedents and consequences of passenger satisfaction with the airport - Bezerra, George C. L. (2020)
There is a growing interest in the passenger experience at the airport. Particularly, the relevance of passenger satisfaction has been emphasized. However, although different research approaches have been used, there is still a gap related to understanding the several relationships between aspects associated with passenger satisfaction with the airport. In this study, a comprehensive conceptual model, which includes the relationships between key antecedents and consequences of passenger satisfaction, was developed and examined. Using structural equation modeling analysis, several findings concerning passenger expectations, airport service quality, switching costs for changing airports, and passenger loyalty towards the airport are stressed